2022
DOI: 10.1097/inf.0000000000003315
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Rather Than Preoperative Neutropenia Is Associated With Early Catheter-related Bloodstream Infections in Newly Diagnosed Pediatric Cancer Patients

Abstract: Background:The relationship of early catheter-related bloodstream infections (CRBSIs) with perioperative neutropenia and antibiotic prophylaxis is not well established. We sought to evaluate perioperative factors associated with early CRBSIs in newly diagnosed pediatric cancer patients, particularly hematologic indices and antibiotic use. Methods: We retrospectively reviewed national registry records of newly diagnosed pediatric cancer patients with port-a-caths inserted using standardized perioperative protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…14,23,24 In this study, ANC below 500 K/µl increased complication rate 1.92 times. Cher et al 25 reported that prolonged neutropenia after catheter insertion, especially in AML, increased early catheter-associated bloodstream infection (CABSI). We did not evaluate the duration of neutropenia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…14,23,24 In this study, ANC below 500 K/µl increased complication rate 1.92 times. Cher et al 25 reported that prolonged neutropenia after catheter insertion, especially in AML, increased early catheter-associated bloodstream infection (CABSI). We did not evaluate the duration of neutropenia in our study.…”
Section: Discussionmentioning
confidence: 99%